Transcription factor FOXD1 and miRNA-204-5p play a major role in B4GALNT2 downregulation in colon cancer - Martina Duca; Nadia Malagolini; Michela Pucci; Virginie Cogez; Anne Harduin-Lepers; Fabio Dall’Olio (Scientific Reports)
Abstract The β1,4-N-acetylgalactosaminyltransferase 2 (B4GALNT2) which synthesizes the histo-blood group antigen Sda is highly expressed by normal colon, but it is dramatically down-regulated in colorectal cancer (CRC). High B4GALNT2 expression in CRC tissues is a marker of longer survival. The molecular bases of B4GALNT2 inhibition in CRC are largely obscure. A key role may be played by transcription factors and miRNA. Through an in silico analysis of The Cancer Genome Atlas and of the Cancer Cell Line Encyclopedia, we identified the transcription factors FOXD1, FOXF2 and PGR as well as mir-204-5p as potential inhibitory agents. Their transient transfection in the cell line GP2d, whose B4GALNT2 is closer to that of a normal mucosa, confirmed their inhibitory activity with a crucial role for FOXD1. The latter inhibited B4GALNT2 also in the middle B4GALNT2 expresser cell line Caco2. Deletion experiments of the putative FOXD1 binding sites in the ~ 2800 bp sequence upstream of the B4GALNT2 transcriptional start site cloned in frame with the luciferase reporter gene, confirmed the regulatory role of FOXD1. Finally, FOXD1 knock down in the non-B4GALNT2 expresser cell line SW948 stimulated B4GALNT2. Thus, FOXD1 and miR-204-5p emerged as crucial new player of B4GALNT2 down-regulation in CRC.